Quality and Reliability Management and Its Applications - Pham, Hoang; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2016)
Integrating development processes, policies, and reliability predictions from the beginning of the product development lifecycle to ensure high levels of product performance and safety, this book helps companies overcome the challenges posed by increasingly complex systems in today's competitive marketplace.   Examining both research on and practical aspects of product quality and reliability management with an emphasis on applications, the book features contributions written by active researchers and/or experienced practitioners in the field, so as to effectively bridge the gap between theory and practice and address new research challenges in reliability and quality management in practice.    Postgraduates, researchers and practitioners in the areas of reliability engineering and management, amongst others, will find the book to offer a state-of-the-art survey of quality and reliability management and practices.
Part I Quality and Reliability - Concepts and Perspectives -- Part II Methods in Reliability Management -- Part III Methods in Quality Management -- Part IV Applications and Practices.
Keywords: Security systems; Industrial Management; Management; Security Science and Technology; Industrial Management; Management